Implementasi Sistem Aplikasi Pengajuan Cuti Karyawan Berbasis Android Pada Security Operation Management - Aris Aris; Nini Santika; Silvia Suhendar (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Currently the process of applying for employee leave is sometimes still semi-computerized so it takes a long time for approval, and do not know the amount of remaining and the history of leave. Therefore, it requires an Android-based application system for staff and managers, as well as for website-based admins. Therefore, the purpose of this research is to make the process of applying for leave faster and reduce the amount of paper used for the approval. The method that will be used to build this application is data collection method by observation, interview and literature study while in the analysis method using PIECES method and system design using UML (Unified Modeling Language), testing using Black Box Testing, programming language that will be used for Android namely Java with Android studio IDE. For web programming use PHP with Visual Studio Code editor and MySQL Database. This research is to facilitate the application of leave by the employee concerned during the approval process and management of data reports.